2021
DOI: 10.34117/bjdv7n9-208
|View full text |Cite
|
Sign up to set email alerts
|

Bioproducts from agro-industrial plant residues: opportunities for sustainable reuse / Bioprodutos de resíduos agroindustriais vegetais: oportunidades ao reaproveitamento sustentável

Abstract: The expansion of agricultural production is increasingly accelerated, as a result of the greater need for food caused by population growth and, consequently, this growth results in the generation of greater amounts of waste. In general, the inspection of public environmental agencies and society demand from agribusinesses actions that increasingly seek the use of new environmental technologies for the destination of production residues, which can drastically reduce the impacts caused to the environment, in add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
1
0
0
Order By: Relevance
“…Bibliographic data demonstrate trends in the development of innovative materials from sugarcane waste with applications in construction , in wastewater treatment (Lebre et al, 2022), and in power generation (Silva et al, 2019), among others. These data are corroborated by Tessmann et al (2021), who identified, by scientometric analysis, the use of sugarcane residues such as bagasse, molasses, straw, cake and vinasse in the production of bioproducts such as lactic acid and flour.…”
Section: Resultssupporting
confidence: 52%
“…Bibliographic data demonstrate trends in the development of innovative materials from sugarcane waste with applications in construction , in wastewater treatment (Lebre et al, 2022), and in power generation (Silva et al, 2019), among others. These data are corroborated by Tessmann et al (2021), who identified, by scientometric analysis, the use of sugarcane residues such as bagasse, molasses, straw, cake and vinasse in the production of bioproducts such as lactic acid and flour.…”
Section: Resultssupporting
confidence: 52%